The Impact of H2S on Obesity-Associated Metabolic Disturbances - Ferran Comas; José María Moreno-Navarrete (MDPI AG, 2021)
Over the last several decades, hydrogen sulfide (H2S) has gained attention as a new signaling molecule, with extensive physiological and pathophysiological roles in human disorders affecting vascular biology, immune functions, cellular survival, metabolism, longevity, development, and stress resistance. Apart from its known functions in oxidative stress and inflammation, new evidence has emerged revealing that H2S carries out physiological functions by targeting proteins, enzymes, and transcription factors through a post-translational modification known as persulfidation. This review article provides a critical overview of the current state of the literature addressing the role of H2S in obesity-associated metabolic disturbances, with particular emphasis on its mechanisms of action in obesity, diabetes, non-alcoholic fatty liver disease (NAFLD), and cardiovascular diseases.